Pain management in the neonatal piglet during routine management procedures. Part 1: a systematic review of randomized and non-randomized intervention studies. (13th June 2014) - Dzikamunhenga, R. S.; Anthony, R.; Coetzee, J.; Gould, S.; Johnson, A.; Karriker, L.; McKean, J.; Millman, S.T.; Niekamp, S. R.; O'Connor, A. M.
Abstract: Routine procedures carried out on piglets (i.e. castration, tail docking, teeth clipping, and ear notching) are considered painful. Unfortunately the efficacy of current pain mitigation modalities is poorly understood. The aim of this systematic review was to synthesize the existing primary scientific literature regarding the effectiveness of pain management interventions used for routine procedures on piglets. The review question was, 'In piglets under twenty-eight days old, undergoing castration, tail docking, teeth clipping, and/or methods of identification that involve cutting of the ear tissue, what is the effect of pain mitigation compared with no pain mitigation on behavioral and non-behavioral outcomes that indicate procedural pain and post-procedural pain?' A review protocol was designed a priori . Data sources used were Agricola (EBSCO), CAB Abstracts (Thomson Reuters), PubMed, Web of Science (Thomson Reuters), BIOSIS Previews (Thomson Reuters), and ProQuest Dissertations & Theses Full Text. No restrictions on year of publication or language were placed on the search. Eligible studies assessed an intervention designed to mitigate the pain of the procedures of interest and included a comparison group that did not receive an intervention. Eligible non-English studies were translated using a translation service. Two reviewers independently screened titles and abstracts for relevance using pre-defined questions. Data were extracted from relevant articles onto pre-defined forms. From the 2203 retrieved citations forty publications, containing 52 studies met the eligibility criteria. In 40 studies, piglets underwent castration only. In seven studies, piglets underwent tail docking only. In one study, piglets underwent teeth clipping only, and in one study piglets underwent ear notching only. Three studies used multiple procedures. Thirty-two trial arms assessed general anesthesia protocols, 30 trial arms assessed local anesthetic protocols, and 28 trial arms assessed non-steroidal anti-inflammatory drugs (NSAIDs) protocols. Forty-one trial arms were controls where piglets received either placebo or no treatment. Forty-five outcomes were extracted from the studies, however only the results from studies that assessed cortisol (six studies), β-endorphins (one study), vocalisations (nine studies), and pain-related behaviors (nine studies) are reported. Other outcomes were reported in only one or two studies. Confident decision making will likely be difficult based on this body of work because lack of comprehensive reporting precludes calculation of the magnitude of pain mitigation for most outcomes.